Photoshop Elements 7: The Missing Manual - Brundage, Barbara (Sebastopol O'Reilly Media, Inc., 2008)
Photoshop Elements 7 includes lots of new tools for sprucing up your photos, like the Scene Cleaner that lets you get rid of unwanted elements and the Smart Brush that makes touch-ups a breeze. But the one thing you won't find in Elements is reader-friendly guidance on how to get the most out of this powerful program. Enter Photoshop Elements 7: The Missing Manual, ready to explain not only how the tools and commands work, but when to use them. With this bestselling book (now in its 5th edition), you'll learn everything from the basics of loading photos into Elements to the new online photo-sha.
Includes Index and Colored Illustrations
Keywords: Adobe Photoshop elements